THE EFFECTIVENESS OF USING YOUTUBE VIDEO IN IMPROVING STUDENTS’ SPEAKING SKILL AT SMA MAHYAJATUL QURRA’ BOARDING SCHOOL LASSANG TAKALAR (PRE-EXPERIMENTAL RESEARCH) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The purpose of this studyis. to determine the effectiveness of using youtube videos in improving students' speaking skills and the problems students find in using youtube video to improve students speaking skill at SMA Mahyajatul Qurra Boarding School, This study used a quantitative method with approach pre-experimental research from the results of research conducted for 4 weeks with 8 meetings showed that using youtube videos effective in improving students' speaking skills at SMA Mahyajatul Qurra Boarding School This can be seen from the post test average value which higher than the pre test (52.73 < 71.64) besides that the statistical calculation of the hypothesis by used paired sample test showedthe value of significant (2-tailed) is 0.00 < 0.05, the null hypothesis (H0) was rejected whereas the alternative hypothesis (H1) was accepted which means there is significant effect of usingYoutube video through asked and answeredquisionnairein teachingprocedure text and the results of this quisionnaire showed that there were no obstacles or problems that students feels by used this method itcan be seen from the last perception ”I have some problem used theyoutubemedia in learning process” and the data saws 40.90% of students choose disagree, 36.36% undecided 18.18% agree and 4.54% strongly disagree. From the resulting questionnaire, some studentsdidn't tend a problem with using the youtube video in the learning process.